2012
DOI: 10.1016/j.neurobiolaging.2011.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Test sequence of CSF and MRI biomarkers for prediction of AD in subjects with MCI

Abstract: Our aim was to identify the best diagnostic test sequence for predicting Alzheimer's disease (AD)-type dementia in subjects with mild cognitive impairment (MCI) using cerebrospinal fluid (CSF) and magnetic resonance imaging (MRI) biomarkers. We selected 153 subjects with mild cognitive impairment from a multicenter memory clinic-based cohort. We tested the CSF beta amyloid (Aβ)1-42/tau ratio using enzyme-linked immunosorbent assay (ELISA) and hippocampal volumes (HCVs) using the atlas-based learning embeddings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 33 publications
4
60
2
Order By: Relevance
“…Evidence has been accumulated to elucidate the predictors of progression to AD in subjects with MCI, which includes investigations of biomarkers obtained in cerebrospinal fluid (CSF), magnetic resonance imaging (MRI), SPECT, and PET. Previous MRI studies have demonstrated that MCI subjects with a smaller volume of the hippocampus [3,4,6] or medial (and inferior) temporal lobe [2,3,5] are at a high risk of progressing to AD. Decreases in regional cerebral blood flow at the precuneus, posterior cingulate [7], or medial temporal lobes [7,8] have been reported to be associated with AD conversion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has been accumulated to elucidate the predictors of progression to AD in subjects with MCI, which includes investigations of biomarkers obtained in cerebrospinal fluid (CSF), magnetic resonance imaging (MRI), SPECT, and PET. Previous MRI studies have demonstrated that MCI subjects with a smaller volume of the hippocampus [3,4,6] or medial (and inferior) temporal lobe [2,3,5] are at a high risk of progressing to AD. Decreases in regional cerebral blood flow at the precuneus, posterior cingulate [7], or medial temporal lobes [7,8] have been reported to be associated with AD conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that a higher risk of AD progression may be involved with an altered function in specific regions such as the posterior cingulate, which are characteristic of AD. Subjects with MCI who developed AD had already exhibited significantly decreased volumes [2][3][4][5][6], decreased levels of regional cerebral blood flow [7,8] and glucose metabolism [5,[9][10][11][12] at the posterior cingulate compared to those who remained in a non-dementia state, when they did not meet criteria for dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of three different datasets produced encouraging results [13][14][15], suggesting that the variability of cutpoints among different studies is low; however, it has been difficult to obtain data from published analyses that could be reanalyzed to confirm this finding.…”
Section: Ad Biomarkers -Csf and Imagingmentioning
confidence: 99%
“…Moreover, diagnostic and prognostic accuracy vary with the position of biomarkers in the amyloid cascade [9]. Amyloid markers have a higher sensitivity for the diagnosis of AD in subjects with MCI than injury markers [4,9,10]. By contrast, injury markers have a better prognostic value than amyloid markers and can predict time to onset of dementia [9].…”
Section: Interpretation Of Ad Biomarker Scoresmentioning
confidence: 99%